If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3p + -3) = -36 Reorder the terms: 3(-3 + 3p) = -36 (-3 * 3 + 3p * 3) = -36 (-9 + 9p) = -36 Solving -9 + 9p = -36 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 9p = -36 + 9 Combine like terms: -9 + 9 = 0 0 + 9p = -36 + 9 9p = -36 + 9 Combine like terms: -36 + 9 = -27 9p = -27 Divide each side by '9'. p = -3 Simplifying p = -3
| -33=-3n+3(-2n-2) | | 33=-3(3p-2) | | 37=1-3(3p-3) | | -28=-4/7y | | 3(2-3m)=33 | | 3(3x+3)-1=35 | | X+0.8x=27 | | (2x-18)+(4x)=180 | | 36=3(3+3x) | | 40x^2-47x+12=0 | | 3-2n-n=6 | | 3p+18=9p | | 2(t+4)-2(2t+3)=-4 | | -2k-3k=5 | | (z^2/6)-(z/2)-84=0 | | T=-16t^2+96t+1 | | 1+3x+x=1 | | 2=1-2m+3m | | 3=-1 | | R(p)=-4p^2+24000p | | 1=n+1+2n | | 2a+3a=-5 | | 75+(4x-9)=180 | | 5(0)=0 | | 3=x-3+2x | | 4+(3+8)=(4+3)+8 | | 1=-3x-3+1 | | H=-16t^2+12t+1700 | | (x-2)/(x^2-x-20) | | (-2/3)*(-4/15)*(45/16) | | 2=1-2m-3m | | n-1-3=-7 |